FEATURES OF THE ORGANIZATION OF FINANCIAL MONITORING IN RUSSIA - Svetlana Mikhailovna Sapozhnikova (Science and Innovation Center Publishing House, 2019)
The article is devoted to an urgent issue – the organization and implementation of financial monitoring in Russia. In the framework of the state’s struggle to suppress activities related to the laundering of proceeds from crime and the financing of terrorism, a three-level financial monitoring system has been created in Russia.